Catheter-free Period Over 2 Days Is Associated with Better Outcome in Catheter-related Bloodstream Infection due to Candida. (4th October 2017) - Matsuo, Takahiro; Mori, Nobuyoshi; Hoshino, Eri; Sakurai, Aki; Furukawa, Keiichi
Abstract: Background: Regardless of active antifungal drugs, mortality of candidemia remains high. Although it is well-known that central venous catheter (CVC) is one of the most important risk factors of candidemia and should be removed immediately, little is known about optimal timing of CVC replacement after removal. Here, we analyzed contributing risk factors associated with 30-day mortality for catheter-related bloodstream infection (CRBSI) due to candida and optimal timing of CVC replacement. Methods: We conducted a retrospective cohort study at St. Luke#129; fs International Hospital between 2004 and 2015. We compared each clinical component in patients who died within 30 days and were alive at 30 days. Also, catheter-free period (from removal to replacement) was compared between group A and B. Fisher#129; fs exact test and Mann–Whitney U test were used in univariate analysis and multivariate linear regression was used for controlling confoundings. Results: Among 228 patients (pts) with candidemia, 166 patients (73%) were on CVC at diagnosis. Of them, 144 patients (65%) removed CVC after the result of candidemia. Seventy-one patients (31%) replaced CVC. Fifteen patients (6%) died within 30 days (group A) and 56 patients (25%) were alive at 30 days (group B). Median age was 74 in group A and 72 in group B ( P = 0.331) (Table 1). In univariate analysis, hematological malignancy (OR 6.75, 95% CI 1.01–44.9) and CVC replacement < 2-days after removal (OR 5.63, 95% CI 1.16–27.3) showed statistically significant increase in group A vs group B (Table 2). In multivariate analysis, CVC replacement < 2-days was independently associated with 30-day mortality (Table 3). Conclusion: This is the first study to demonstrate the optimal timing of CVC replacement in CRBSI due to candida. CVC replacement < 2 days was an independent risk factor for 30-day mortality. Disclosures: All authors: No reported disclosures.